2019
DOI: 10.3390/s19081784
|View full text |Cite
|
Sign up to set email alerts
|

Sperm-Cultured Gate Ion-Sensitive Field-Effect Transistor for Non-Optical and Live Monitoring of Sperm Capacitation

Abstract: We have successfully monitored the effect of progesterone and Ca2+ on artificially induced sperm capacitation in a real-time, noninvasive and label-free manner using an ion-sensitive field-effect transistor (ISFET) sensor. The sperm activity can be electrically detected as a change in pH generated by sperm respiration based on the principle of the ISFET sensor. Upon adding mouse sperm to the gate of the ISFET sensor in the culture medium with progesterone, the pH decreases with an increasing concentration of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…As a result, a change in the interfacial potential between the solution and the oxide membrane surface is output as the Nernstian response for the change in pH, which is ideally calculated as 59.2 mV/pH at 25°C. Cellular respiration activities were monitored at a cell/ gate nanogap interface using a pH-sensitive FET in a real-time and noninvasive manner [21][22][23][24][25][26][27]. When polyvinyl chloride (PVC)-based ISMs with ionophores are coated on a gate insulator, the Nernstian response is similarly obtained for the change in the potential at the solution/ISM interface with ions of various concentrations (e.g., Na + and K + ) [1,16,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, a change in the interfacial potential between the solution and the oxide membrane surface is output as the Nernstian response for the change in pH, which is ideally calculated as 59.2 mV/pH at 25°C. Cellular respiration activities were monitored at a cell/ gate nanogap interface using a pH-sensitive FET in a real-time and noninvasive manner [21][22][23][24][25][26][27]. When polyvinyl chloride (PVC)-based ISMs with ionophores are coated on a gate insulator, the Nernstian response is similarly obtained for the change in the potential at the solution/ISM interface with ions of various concentrations (e.g., Na + and K + ) [1,16,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the ISFET sensor would have detected the change in pH on the basis of the equilibrium reaction between hydrogen ions and hydroxyl groups at the oxide gate insulator. Basically, the ISFET sensors used in this study showed a sensitivity of about 55 mV/pH [32], as shown in Figure S4 in the Supplementary Materials S6. In accordance with the electrical properties of the ISFET sensors, the streptavidin–biotin interaction on the magnetic beads was assumed to be detected as the change in interfacial pH at the magnetic beads/gate insulator nanogap interface by the MCC method.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, these results were verified using the cultured-cell-coupled gate ISFET sensor in real time. 3540 Figure 4c shows Δ V out for cancer and normal cells during cell culture. 39 The culture medium was replaced with a fresh one at 0 h in this graph.…”
Section: Cultured-cell-coupled Gate Fetsmentioning
confidence: 99%